PREFIX PROCESS IN LEXICAL MORPHOLOGY - Abd. Muin (UIN Alauddin Makassar, 2013)
ABSTRACTLearning vocabulary is difficult thing to remember, therefore, this writing tries to give solution that the learner should study the affixation process in English. There are two kinds of affixation, first, the bound morpheme comes after root is called suffix, and secod one, the bound morpheme comes before root is called prefix. But if we expalion both of them look too broad, Therefore, the writer just focuses on prefix process in English relating with negative and positive prefixes. The examples of negative prefixes are un, in, im, dis, mis, ill, ir and anti, while positive ones such as re, out, super, under, multi and over.ABSTRAKPelajaran kosakata adalah hal yang sulit untuk diingat; oleh karena itu, tulisan ini mencoba memberikan solusi bahwa pelajar harus mempelajari proses afiksasi dalam bahasa Inggris. Ada dua jenis afiksasi; pertama, morfem terikat terdapat setelah root disebut suffix, dan kedua, morfem terikat berada terdapat root disebut prefix. Tetapi jika kita menjelaskan keduanya tampak terlalu luas, karena itu, penulis hanya berfokus pada proses awalan dalam bahasa Inggris yang berkaitan dengan prefiks negatif dan positif. Contoh-contoh dari prefiks negatif adalah un, di, im, dis, mis, ill, ir dan anti, sementara yang positif seperti re, out, super, under, multi dan over.